UV-C treatment for hepatitis A Virus inactivation in Ulva lactuca edible seaweed - Pantu Kumar Roy; Anamika Roy; Eun Bi Jeon; Shin Young Park (Applied Food Research)
The presence of hepatitis A virus (HAV) contamination stands as a notable contributing factor to acute hepatitis, sometimes leading to acute liver failure. HAV transmission is predominantly associated with the ingestion of water and food contaminated with the virus, as well as through sexual contact among men who engage in sexual activity. The effectiveness of UV-C on the viable reduction of a HAV strain on edible seaweed Ulva lactuca was tested at different conditions (control, 72, 216, 360, and 504 mWs/cm2 of UV-C dose) and the result of treatment on seaweed quality. To identify infectious and noninfectious virus components, the HAV was exposed using RT-qPCR with propidium monoazide/sarkosyl. HAV was decreased in seaweed when treatment with UV-C (control, 72, 216, 360, and 504 mWs/cm2) in non-PMA (0.94, 1.09, 1.67, and 2.32 log) and PMA + Sarkosyl-treated (1.03, 1.47, 1.94, and 3.02 log) reduction titers, respectively. The pH and Hunter color of the control and UV-C exposure seaweed were exhibited significant different (P > 0.05), while but sensory characteristics not significantly different. These results suggest the potential utility of PMA/RT-qPCR in identifying HAV infectivity without compromising the quality of seaweed following UV-C treatment. HAV can be inactivated in the food matrix at commercially satisfactory treatment of UV-C 504 mWs/cm2.